Hubungan Sales Promotion Shopee dengan Minat Beli Mahasiswa di Kota Bandung - Nadhira Andriani; Satya Indra Karsa (Bandung Conference Series: Communication Management, 2022)
Abstract. This research is entitled "The Correlation of Sales Promotion X with Buying Interest of Students in Bandung City" Correlational Study Between Sales Promotion X and Buying Interest of Students of Bandung State Polytechnic and Bandung Islamic University. This study aims to determine the extent of the relationship between sales promotion X and student buying interest. Because X often gives or offers promos whose purpose is to make consumers interested in shopping at X. This research method uses a quantitative correlation approach. Data collection techniques in this study used a questionnaire or a questionnaire and literature study. The population in this study were active students using X at the Bandung State Polytechnic and Islamic University of Bandung. The sample in this study amounted to 100 respondents. The results of the discussion in this study are that there is a fairly strong relationship between X Sales Promotion and Buying Interest of Students in Bandung. Abstrak. Penelitian ini berjudul “Hubungan Sales Promotion X dengan Minat Beli Mahasiswa di Kota Bandung” Studi Korelasional Antara Sales Promotion X Dengan Minat Beli Mahasiswa Politeknik Negeri Bandung dan Universitas Islam Bandung. Penelitian ini bertujuan untuk mengetahui sejauh mana hubungan sales promotion X dengan minat beli mahasiswa. Karena X sering sekali memberikan atau menawarkan promo-promo yang tujuannya agar konsumen berminat berbelanja di X. Metode penelitian ini menggunakan pendekatakan kuantitatif korelasi. Teknik pengumpulan data dalam penelitian ini menggunakan angket atau kuesioner dan studi kepustakaan. Adapun populasi dalam penelitian ini adalah Mahasiswa aktif Pengguna X di Politeknik Negeri Bandung dan Universitas Islam Bandung. Sampel dalam penelitian ini berjumlah 100 responden. Hasil dari pembahasan dalam penelitian ini adalah terdapat hubungan yang cukup kuat antara Sales Promotion X dengan Minat Beli Mahasiswa di Kota Bandung.